Venetoclax in myeloma: to B, or not to B - Raab, Marc-Steffen (Blood, 2024)
By applying single-cell epigenetics and transcriptomics, Leblay et al1 reveal in this issue of Blood that cellular lineage plasticity, due to a switch from a B-cell-like phenotype to a more canonical plasma cell-like state, contributes to drug-acquired resistance in patients with t(11;14)-positive multiple myeloma (MM) receiving venetoclax.Venetoclax is an oral BH3 mimetic that effectively displaces proapoptotic proteins from the inhibitor of apoptosis B-cell lymphoma 2 (BCL-2). This compound has become standard of care, as a single agent and in combinations, in chronic lymphocytic leukemia (CLL) and, more recently, in acute myeloid leukemia. In MM, a phase 1 study showed promising efficacy as monotherapy in patients harboring a t(11;14) translocation, whereas initial results from the combination of venetoclax with the proteasome inhibitor, bortezomib, initially raised hope for its efficacy in non-t(11;14) patients.2,3 The phase 3 placebo-controlled BELLINI study did not show superior outcomes for this combination compared with bortezomib and dexamethasone, mainly due to higher mortality in patients receiving venetoclax. However, subgroup analyses revealed higher response rates and longer progression-free survival for t(11;14) patients and those with high expression of BCL-2.4 The first results of the ongoing registration phase 3 CANOVA trial of either venetoclax or pomalidomide in combination with dexamethasone in patients with a t(11;14) translocation are expected later this year.
Gesehen am 24.05.2024